The Most Influential Aspects of the Phenomenon Public Space in Jalan Wisata Kerto Menanggal - Shabrina Nareswara; Purwanita Setijanti; Murni Rachmawati (Institut Teknologi Sepuluh Nopember, 2020)
Public space is one of the important components in the city and participates in improving the quality of life of the people in a city. The city of Surabaya as the capital of East Java with high public space development needs, often the development of public space is more concentrated in the city center. The Public Space of Menanggal Tourism Road located on the border of Surabaya City and Sidoarjo Regency is experiencing a phenomenon that causes a decrease in the image of the region and abuse of the function of public facilities. Behavior of users of public space at the time of the phenomenon is the key to the occurrence of the problem. Therefore an appropriate theoretical approach is needed to understand the phenomenon as a whole. Behavior setting is an approach that connects activity patterns and behavior patterns in a physical environment that is used to understand the phenomenon. This research uses naturalistic paradigms and qualitative strategies with data collection techniques using observation and in-depth interviews. To identify the aspects that most influence on the formation and continuity of the phenomenon of the Tourism Road Region to date these data, data analysis using the Miles and Huberman model is used. The results showed that the affective meaning and activity system were the most influential aspects in the continuity of the phenomenon. These aspects can be used as a basis for developing concepts to overcome the problems that arise during the phenomenon.